2012
DOI: 10.4103/0970-9371.93228
|View full text |Cite
|
Sign up to set email alerts
|

Mucinous carcinoma of the male breast with axillary lymph node metastasis: Report of a case based on fine needle aspiration cytology

Abstract: Pure mucinous carcinoma of the male breast is an uncommon malignant breast neoplasm and extremely rare is its metastasis in axillary lymph nodes. Most of these cases have been diagnosed after surgical resection with only a few cases diagnosed on fine needle aspiration cytology (FNAC). Although FNAC is well established in the evaluation of breast masses in females there are few reports in males. We are presenting a case of pure mucinous carcinoma of the male breast with metastasis in axillary lymph nodes in a 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
1
6
0
1
Order By: Relevance
“…The cytological features of mucinous carcinoma include the presence of relatively uniform neoplastic cells with slightly enlarged round to oval nuclei containing small nucleoli arranged in cords or small nests, within a rich mucinous material ( 11 ). A few cases of mucinous carcinoma of the male breast successfully diagnosed by FNA have been reported ( 8 , 12 – 14 ), although FNA was not performed in the present case. Recently, Ingle et al documented a case of pure mucinous carcinoma with axillary lymph node metastasis in a 75-year-old male ( 8 ).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The cytological features of mucinous carcinoma include the presence of relatively uniform neoplastic cells with slightly enlarged round to oval nuclei containing small nucleoli arranged in cords or small nests, within a rich mucinous material ( 11 ). A few cases of mucinous carcinoma of the male breast successfully diagnosed by FNA have been reported ( 8 , 12 – 14 ), although FNA was not performed in the present case. Recently, Ingle et al documented a case of pure mucinous carcinoma with axillary lymph node metastasis in a 75-year-old male ( 8 ).…”
Section: Discussionmentioning
confidence: 74%
“…Therefore, certain researchers have suggested that axillary lymph node dissection may be unnecessary for pure mucinous carcinoma, and they recommend sentinel lymph node dissection instead for patients with this form of tumor ( 6 ). However, certain cases of pure mucinous carcinoma with axillary lymph node metastasis in the male breast have been reported ( 5 , 8 , 9 ), and a case of pure mucinous carcinoma with lung metastasis in the male breast has also been documented ( 10 ). Thus, sentinel lymph node technique and clinical follow-up are considered necessary for patients with mucinous carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Review of the literature revealed majority of the published literature pertaining to the cytological diagnosis MC are single case reports with only few series available. [6][7][8][9][10] Adhikari et al 7 studied eight cases of MC (5 PMC + 3 MMC) and observed presence of ECM along with single and cluster of tumor cells floating in them and thin walled capillaries as prominent features in five cases of PMC. Three cases of MMC showed in addition to mucin, pleomorphic clusters of tumor cells (as observed in our study).…”
Section: Discussionmentioning
confidence: 99%
“…It constitutes approximately 5% of all breast cancers in men, compared with 1%-2% in women with breast carcinomas (24). Non-Hodgkin lymphoma, malignant melanoma, oncocytic carcinoma, secretory carcinoma, mucinous carcinoma, and metaplastic carcinoma have been rarely reported (1,18,20,(24)(25)(26)(27)(28). Metastatic involvement of male breasts with SCC and melanoma are also identified sporadically (26).…”
Section: Discussionmentioning
confidence: 99%